Traditional Medicine in Uganda : Historical Perspective, Challenges and Advances - World Bank (Washington, DC, 2012)
Traditional medicine refers to the ways that existed of protecting and restoring health before the arrival of modern medicine (World Health Organization - WHO 1996). It has also been defined as the sum total of all knowledge and practices used in the prevention, diagnosis, and elimination of physical, mental or social imbalances and which relies exclusively on practical experience and observation handed down from generation to generation, whether orally or in writing. It has bee debated whether the word traditional should be used at all, as it implies some degree of stagnancy or backwardness.